Dampak Peredaran Obat Ilegal Lintas Negara terhadap Kesehatan Masyarakat Global dan Strategi Penanggulangannya - Meilinasary, Khairunnisa Azani; Malindea, Chinda; Athirah; Andriani, Yeni; Shofiaa, Lulu Dhiya (Pharmaceutical Journal, 2025)
The World Health Organization (WHO) established an international organisation  known as the Member State Mechanism, aimed at combating the circulation of falsified  and substandard medicines to ensure that the global population has access to high-quality,  safe, and affordable medicines. Indonesia, as one of the member countries, has  consistently taken an active role in this forum. However, in reality, both Indonesia and  other countries around the world have not yet succeeded in overcoming this issue. The  widespread circulation of falsified and substandard medicines poses significant risks to  global public health. The objective of this study is to examine the impact of falsified and  substandard medicines on global public health and to analyze the efforts undertaken by  Indonesia and other countries to handle the proliferation of these medicines. This article  employs a qualitative research method with an explanatory approach. The concepts of  international cooperation and international regimes are used to explain the outcomes of  collaboration within the Member State Mechanism and the role of WHO as an  international organization in supporting efforts to combat counterfeit medicines. The  result of this study is to illustrate the negative impacts caused by the circulation of  falsified and substandard medicines, as well as the challenges faced by Indonesia and  other countries in addressing the issue. These challenges stem from two main sources:  external factors related to international cooperation, and internal factors stemming from  domestic conditions.